1992
DOI: 10.1210/en.130.3.1145
|View full text |Cite
|
Sign up to set email alerts
|

Antiestrogens prevent the stimulatory effects of L-triiodothyronine on cell proliferation

Abstract: This paper studies the modulatory effects of two antiestrogens, the steroid ICI 164 384 and the nonsteroidal compound 4-hydroxytamoxifen (4-OH-tam), on the proliferation of L-T3-stimulated cell lines. Three cell lines known to be stimulated by thyroid hormones and to contain estrogen receptors but to have a different estradiol sensitivity to estradiol were used; F4Z2 and MCF-7 cells were stimulated, whereas GH3 cells were insensitive. Cells were counted 6-7 days after hormones and antihormones were added to th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
14
2

Year Published

1996
1996
2012
2012

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 27 publications
(22 citation statements)
references
References 0 publications
6
14
2
Order By: Relevance
“…TR are also present in human breast cancer cell lines (Burke and McGuire, 1978;Zhou-Li et al, 1992), but con¯icting reports describe both mitogenic and antimitogenic e ects of T3 (Nogueira and Brentani, 1996;MartõÂ nez et al, 2000). A role of T3 in the physiology of ®brocystic breast disease has been suggested (MartõÂ nez et al, 1995).…”
Section: Discussionmentioning
confidence: 99%
“…TR are also present in human breast cancer cell lines (Burke and McGuire, 1978;Zhou-Li et al, 1992), but con¯icting reports describe both mitogenic and antimitogenic e ects of T3 (Nogueira and Brentani, 1996;MartõÂ nez et al, 2000). A role of T3 in the physiology of ®brocystic breast disease has been suggested (MartõÂ nez et al, 1995).…”
Section: Discussionmentioning
confidence: 99%
“…Manipulations of thyroid hormones and estrogen in vitro potentiate or mutually inhibit effects on gene expression (2)(3)(4). Our data presented in the accompanying paper (5) demonstrates that both TRs and ERs are present in rat hypothalamic nuclear extracts and both can bind to a preproenkephalin (PPE) promoter ERE.…”
mentioning
confidence: 93%
“…Studies over the past decade have demonstrated marked functional crosstalk between receptor systems (Bunone et al 1996). In this respect, tri-iodothyronine (T 3 )-induced growth of GH 3 cells has been shown to be inhibited by antioestrogens (Zhou-Li et al 1992). Similarly, the synthetic glucocorticoid, dexamethasone (Dex), has been shown to inhibit both oestrogen-and T 3 -induced growth of GH 3 cells (Zhou-Li et al 1991).…”
Section: Introductionmentioning
confidence: 99%